PENGARUH PROFITABILITAS, LIKUDITAS DAN LEVERAGE TERHADAP FINANCIAL DISTREESS - Feri Irawa; Suyanto Suyanto (Jurnal GeoEkonomi, 2023)
The purpose of this study is to analyze and detect empirical evidence about the effect of profitability, liquidity and leverage on financial distress simultaneously and partially in banking companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This type of research is using quantitative. In the study there were 3 independent variables namely profitability (ROA), liquidity (CR) leverage (DAR) and the dependent variable namely financial distress (ICR). The population uses all banking companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sample was determined using a purposive sampling technique so that there were 20 companies. The analytical method using logistic regression states that profitability, liquidity and leverage have a negative effect on financial distress.